Worldwide board reforms and cross-border M&A flows - Dong, Qi; Marcato, Gianluca; Zheng, Chen (Journal of Corporate Finance, 2026)
This study examines the influence of global board reforms on cross-border mergers and acquisitions (CBMAs). Using a difference-in-differences methodology, we find that CBMA flows increase significantly following board reforms in both home and host countries. The effect is more pronounced for countries with relatively weaker external governance mechanisms compared to their counterparts. Our findings suggest that board reforms enhance board functions, thereby facilitating firms' outbound investments. Simultaneously, improved board governance mitigates acquisition risks, attracting inward investments and, consequently, stimulating CBMA flows.